Revisiting the last four decades of discussion on artificial intelligence in accounting literature: Assessing past and guiding for future research - Pamungkas, Sigit; Nani, Dhiona Ayu (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This study explores the collection of research articles on AI in an accounting context, particularly on publications covering business, management, and accounting. We analyzed nearly 40 years of research history, attempting to identify relevant publications from the earliest to most recent in the data retrieved from the database and reviewed in this study. A systematic literature review is conducted to analyze 78 selected articles retrieved from the Scopus Database over the last four decades. Content analysis is applied to identify prospective future research avenues. The findings show a significant growth of articles in the last decade (2011 and after). This fact confirms that AI is becoming one of the main spotlights in accounting research. The results reveal that the current discussion of AI in the accounting literature is dominated by studies around the AI approach, with much conversation on auditing and financial accounting topics about AI technology. We suggest that future accounting studies be conducted more at the AI task and application levels. This study also marked topics in the accounting fields rarely discussed about AI, including public sector accounting and accounting education. This study clusters the literature into the accounting domains (auditing, finance, managerial, tax, and accounting information systems) and the AI technology domains (approach, tasks, and applications).